2021
DOI: 10.1093/jn/nxab144
|View full text |Cite
|
Sign up to set email alerts
|

Different Food Sources of Fructose-Containing Sugars and Fasting Blood Uric Acid Levels: A Systematic Review and Meta-Analysis of Controlled Feeding Trials

Abstract: Background Although fructose as a source of excess calories increases uric acid, the effect of the food matrix is unclear. Objectives To assess the effects of fructose-containing sugars by food source at different levels of energy control on uric acid, we conducted a systematic review and meta-analysis of controlled trials. Methods MEDLINE, Embase, and the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 106 publications
2
13
0
Order By: Relevance
“…It is unknown whether the effects seen for SSBs providing excess energy hold for other important food sources of fructose-containing sugars at different levels of energy control on NAFLD markers. There is evidence on other cardiometabolic outcomes that the harmful effects seen for SSBs do not hold for other food sources of fructose-containing sugars, whereas some (fruit) may even show benefit [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown whether the effects seen for SSBs providing excess energy hold for other important food sources of fructose-containing sugars at different levels of energy control on NAFLD markers. There is evidence on other cardiometabolic outcomes that the harmful effects seen for SSBs do not hold for other food sources of fructose-containing sugars, whereas some (fruit) may even show benefit [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of harm observed for SSBs alone at all levels of energy control is supported by a previous systematic review and meta-analysis including 7 trial comparisons of fructose versus glucose which showed no overall effect [ 121 ]. Previous systematic reviews and meta-analyses exploring the effect of different food sources of fructose containing sugars on cardiometabolic outcomes in controlled trials have demonstrated harm when SSBs are consumed as a source of excess calories, including on glycemic control, adiposity, blood pressure and uric acid [ 8 , 11 , 139 , 140 ]. It is possible that the lack of harm observed in the present analysis may be the result of fewer trials and those which only comprised of healthy participants free of chronic diseases and with low baseline CRP levels (median 0.4 mg/L, range 0.2–1.22 mg/L).…”
Section: Discussionmentioning
confidence: 99%
“…Bioactives, including antioxidants and flavonoids, may also interfere with fructose metabolism. For example, antioxidants and flavonoids may reduce oxidative stress and thus fructose-induced uric acid production [ 143 ], which is supported by the lack of harm observed for fruit and fruit juice in a systematic review and meta-analysis of food sources of fructose-containing sugars on uric acid which contrasts the significant increases in uric acid that were observed for SSBs [ 8 ]. In addition to bioactives as mechanisms through which various foods may influence inflammation, these food sources of fructose-containing sugars can be higher in dietary fibre and lower in glycemic index (GI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, orange juice might possibly exert acute and sustainable improvements of cardiovascular health. 74,75 Recently, a systematic review and meta-analysis of controlled feeding trials has corroborated the decreasing effect on uric acid by 100% fruit juice consumption, 76 although a weak but opposite effect had been seen earlier in prospective cohort studies. 77 D'Elia et al 78 reported a systematic review and meta-analyses that found a number of favorable associations of 100% fruit juice intake and cardiovascular health or risk factors.…”
Section: ■ Introductionmentioning
confidence: 99%